High-temperature electrochemical energy conversion and storage : fundamentals and applications - Shi, Yixiang (CRC Press, Taylor & Francis Group, 2018)
"As global demands for energy and lower carbon emissions rise, developing systems of energy conversion and storage becomes necessary. This book explores how Electrochemical Energy Storage and Conversion (EESC) devices are promising advanced power systems that can directly convert chemical energy in fuel into power, and thereby aid in proposing a solution to the global energy crisis. The book focuses on high-temperature electrochemical devices that have a wide variety of existing and potential applications, including the creation of fuel cells for power generation, production of high-purity hydrogen by electrolysis, high-purity oxygen by membrane separation, and various high-temperature batteries. High-Temperature Electrochemical Energy Conversion and Storage: Fundamentals and Applications provides a comprehensive view of the new technologies in high-temperature electrochemistry. Written in a clear and detailed manner, it is suitable for developers, researchers, or students of any level."--Provided by publisher
Keywords: Direct energy conversion.; High temperature electrolysis.; Energy storage.; elektronické knihy; electronic books